1986
DOI: 10.1093/nar/14.15.5981
|View full text |Cite
|
Sign up to set email alerts
|

Infectious mutants of cassava latent virus generatedin vivofrom intact recombinant DNA clones containing single copies of the genome

Abstract: Intact recombinant DNAs containing single copies of either component of the cassava latent virus genome can elicit infection when mechanically inoculated to host plants in the presence of the appropriate second component. Characterisation of infectious mutant progeny viruses, by analysis of virus-specific supercoiled DNA intermediates, indicates that most if not all of the cloning vector has been deleted, achieved at least in some cases by intermolecular recombination in vivo between DNAs 1 and 2. Significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
2

Year Published

1988
1988
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 28 publications
5
50
2
Order By: Relevance
“…The coat protein caused a significant (30-40 %) reduction in complementary-sense gene expression. Although it is known that the coat protein affects the relative levels of ssDNA and dsDNA (Stanley & Townsend, 1986;Sunter et al, 1990), its influence on gene expression has not been reported previously. While it is possible that the coat protein has a specific effect on complementary-sense expression, it could cause a general reduction in the level of gene expression simply as a result of its ability to bind to dsDNA (Ingham et al, 1995), in this instance to the GUS expression cassettes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The coat protein caused a significant (30-40 %) reduction in complementary-sense gene expression. Although it is known that the coat protein affects the relative levels of ssDNA and dsDNA (Stanley & Townsend, 1986;Sunter et al, 1990), its influence on gene expression has not been reported previously. While it is possible that the coat protein has a specific effect on complementary-sense expression, it could cause a general reduction in the level of gene expression simply as a result of its ability to bind to dsDNA (Ingham et al, 1995), in this instance to the GUS expression cassettes.…”
Section: Discussionmentioning
confidence: 96%
“…Virion-sense gene A V1 encodes the coat protein (Townsend et al, 1985). A function has yet to be assigned to the overlapping gene, A V2, and neither virion-sense gene is required for systemic infection of Nicotiana benthamiana (Stanley & Townsend, 1986;Etessami et al, 1989). Of the four overlapping complementary-sense genes, AC1 is essential for viral DNA replication (Brough et al, 1988;Elmer et al, 1988;Etessami et al, 1991), AC2 transactivates the expression of coat protein and DNA B genes (Haley et al, 1992; and AC3 is required for normal levels of viral DNA replication (Sunter et al, 1990;Etessami et al, 1991;Morris et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The alterations included an increased diameter of the intersymplastic channel sufficient to allow virus particles to pass through and, in many cases, virus particles were observed within the channel. The presence of virus particles free in the cytoplasm and en route between cells argues strongly that such particles mediate the spread of infection in these tissues, although it cannot be excluded that other forms of nucleoprotein, or nucleic acid, may also be involved, particularly as isolates of tobacco rattle virus (Lister, 1966) or cassava latent virus (Stanley & Townsend, 1986) that lack coat protein can infect plants systemically.…”
Section: Discussionmentioning
confidence: 99%
“…Several experiments in which components of bipartite geminiviruses were exchanged (pseudorecombination) have been recently reported yon Arnim & Stanley, 1992). This pseudorecombination mechanism can now be added to the intermolecular recombination reported for ACMV (Etessami et al, 1989;Klinkenberg et at., 1989;Stanley & Townsend, 1986). Both mechanisms, independently or acting in a concerted manner, might be important in nature for the generation of new viruses.…”
Section: Torres-pacheco and Othersmentioning
confidence: 99%